Deuteron nuclear interaction potential with heavy nuclei in single folding model - O. V. Babak; V. P. Verbytskyi; O. D. Grygorenko (Ядерна фізика та енергетика)
Deuteron interaction potential with heavy nuclei at sub-barrier energies has been constructed in the frame-work of single folding model using the complex dynamic polarization potential. It is shown that the account of finite deuteron size leads to significant increasing of nuclear potential in outer region of interaction. Cross sec-tions of deuteron elastic scattering on 208Pb at energy 7, 7.3 and 8 MeV were calculated and compared with ex-periment data. Calculations were performed without any variations of parameters.